Searching for calcium‐aluminum‐rich inclusions in cometary particles with Rosetta/COSIMA. (24th May 2016) - Paquette, John A.; Engrand, Cecile; Stenzel, Oliver; Hilchenbach, Martin; Kissel, Jochen; ,
Abstract: The calcium‐aluminum‐rich inclusions (CAIs) found in chondritic meteorites are probably the oldest solar system solids, dating back to 4567.30 ± 0.16 million years ago. They are thought to have formed in the protosolar nebula within a few astronomical units of the Sun, and at a temperature of around 1300 K. The Stardust mission found evidence of CAI‐like material in samples recovered from comet Wild 2. The appearance of CAIs in comets, which are thought to be formed at lower temperatures and larger distances from the Sun, is only explicable if some mechanism allows the efficient transfer of such objects from the inner solar nebula to the outer solar nebula. Such mechanisms have been proposed such as an X‐wind or turbulence. In this work, particles collected from within the coma of comet 67P/Churyumov–Gerasimenko are examined for compositional evidence of the presence of CAIs. COSIMA (the Cometary Secondary Ion Mass Analyzer) uses secondary ion mass spectrometry to analyze the composition of cometary dust captured on metal targets. While CAIs can have a radius of centimeters, they are more typically a few hundred microns in size, and can be smaller than 1 μm, so it is conceivable that particles visible on COSIMA targets (ranging in size from about 10 μm to hundreds of microns) could contain CAIs. Using a peak fitting technique, the composition of a set of 13 particles was studied, looking for material rich in both calcium and aluminum. One such particle was found.